(untitled) (Journal of Enam Medical College, 2025)
Background: Lipid abnormalities have an important biochemical basis in the disease process of adult nephrotic syndrome patients. Dyslipidemia in nephrotic syndrome involved in the cardiovascular risk and also accelerates the progression of glomerular dysfunction. Higher plasma concentration of low density lipoprotein cholesterol (LDL-C) in nephrotic syndrome is a driving force for atherosclerotic disease as well as the high cardiovascular related mortality. This study is designed to evaluate the association between serum LDL-C level with 24 hour urinary total protein(UTP) and serum albumin concentration. Materials and Methods: This cross-sectional anlytical study was carried out in the Department of Biochemistry, Dhaka Medical College, Dhaka during the period of July 2013 to June 2014. A total 50 (fifty) study subjects with age range from 20-50 years of both sexes were enrolled as diagnosed adult nephrotic syndrome patients from the Dept. of Nephrology, Dhaka Medical College, Dhaka. With baseline information, serum LDL-C level, serum albumin level and 24 hour urinary total protein of study subjects were estimated. Mean values of the variables were determined. Correlation between variables were determined by Pearson’s correlation test by using SPSS for windows version 20.0. For all the statistical analysis p<0.05 was considered as significant. Results: Mean (±SD) value of serum LDL-C, in adult nephrotic syndrome patients was 231.16±34.28 mg/dl. Mean value of 24 hour urinary total protein in study subjects was 5.65±0.54 gm/24 hours. Mean value of serum albumin levels in study subjects was 1.87±0.54 gm/dl. Positive correlation was found between 24 hour urinary total protein and LDL-C, (r=0.444) (p<0.05). Negative correlation was found between S. albumin and LDL-C, (r= -0.321) (p<0.05).Conclusion: Increased level of serum LDL-C in adult nephrotic syndrome, possesses a significant relationship with increased proteinuria and decreased serum albumin concentration, which could predispose abnormalities in lipid metabolism, leading to develop coronary artery disease. J Enam Med Col 2022; 12(3): 143−147